NILAI MORAL DALAM FILM HELLO GHOST KARYA KIM YOUNG TAK (KAJIAN ANALISIS ISI) - Mita Sari Sapitri; Sumiharti Sumiharti; Sainil Amral (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research was motivated by finding moral values in the film Hello Ghost by Kim Young Tak (Content Analysis Study). This research aims to explain moral values related to human-human relationships in the form of aspects of caring for others, aspects of mutual help, aspects of deliberation, aspects of living in harmony, aspects of forgiveness, aspects of keeping promises, and aspects of respecting other people. It is hoped that this can convey various deep messages to change human thinking patterns. This research uses a qualitative descriptive method, namely analyzing data in the form of words related to human behavior which describes moral values in aspects of human relations in the film Hello Ghost by Kim Young Tak. The author got the research data from dialogue quotes in films with the aspects to be studied. Based on the results of the research that has been carried out, it is obtained from the quotation data for the aspect of caring for others as many as 29 quotations, the aspect of helping each other as many as 10 quotations, the aspect of deliberation as many as 2 quotations, the aspect of living in harmony as many as 2 quotations, the aspect of forgiveness as many as 3 quotations, the aspect of keeping promises as many as 4 quotations, and appreciate others as many as 8 quotes. The aspect of moral values that is more dominant in this film is caring for others and the aspect that is found less in this film is the aspect of living in harmony and deliberation. The moral values in this film are the solution to various problems. The moral values that the author obtains can be used as an example in everyday life.